Historia Sicut Prophetia: Re-Reading Joseph Ratzinger in the Light of His Habilitationsschrift on St Bonaventure - Crozier, William (Irish theological quarterly, 2025)
This article explores Joseph Ratzinger’s account of Bonaventure’s theological development in his Habilitationsschrift: The Theology of History in St Bonaventure. It shows that there are several parallels between the intellectual transitus which Ratzinger attributes to Bonaventure during the 1260s and 1270s and his own much studied intellectual journey. Ratzinger portrays Bonaventure as a thinker who, because of a series of crises at the University of Paris shifted from a sympathetic engagement with the Peripatetic and Thomist schools to a much more critical, openly hostile, attitude towards them. While much has been made of Ratzinger’s Bonaventurian heritage, this article argues that his relationship with the Franciscan possesses a dimension that goes beyond simple indebtedness: in his Habilitationsschrift, Ratzinger presents us with a blueprint of what was to be his own future development and, more importantly, a new way of approaching the controversial question of whether his core theological ideas changed.